Propuesta de Mejora del Sistema de Gestión de Mantenimiento en la Empresa Transportliquidos S.A.S (2022)
Given the current competitive scenario, global business trends recognize innovation and creativity as fundamental elements to stay afloat; however, the companies in the transforming link of the Colombian dairy sector require more work in innovation and creativity.